The Study of Personal Hygiene and The Existence of Sarcoptes Scabiei in The Sleeping Mats Dust and Its Effects on Scabiesis Incidence Amongst Prisoners at IIB Class Penitentiary, Jombang District - Arie Aulia Nur Affandi (Universitas Airlangga, 2019)
Scabiesis is a highly contagious skin disease caused by Sarcoptes scabiei from hominis mite variant. This disease frequently attacks groups of humans and who live together such as in penitentiary. This study aims to identify the correlation between personal hygiene and the existence of Sarcoptes scabiei on sleeping mats dust with the incidence of scabiesis infection amongst prisoners at IIB Class Penitentiary, Jombang, Indonesia. The design of this study was cross sectional. The population in this study were 638 persons with the sample size of 85 participants obtained by adopting stratified random sampling method. The statistical analysis used to find correlation between variables was Chi Square test. The results showed that most of respondents (65.9%) had good personal hygiene. There were 5 samples of dust on prisoner's sleeping mats found with positive Sarcoptes scabiei. Based on examination by doctors, most of respondents suffered from scabiesis (74.1%). Chi square test results showed that there was a significant correlation between personal hygiene and the incidence of scabies with P value (0.001) < α(0.05) and there was no significant correlation between the existence of Sarcoptes scabiei in sleeping mats dust and scabiesis incidence with P value (0.321) > α(0.05). The conclusion of this study was that most respondents already have good personal hygiene, and only the cleanliness of hands and feet were still not good. The results of the dust sample on sleeping mats showed that the existence of Sarcoptes scabei were low However, these findings do not undermine the alertness that sleeping mats has a potential risk sources of scabiesis transmission in penitentiary. Counseling about personal hygiene should be improved, especially hand and feet hygiene. Eradication of scabiesis should be done thoroughly for larger population not only for scabiesis sufferers.